2021
DOI: 10.2196/28416
|View full text |Cite
|
Sign up to set email alerts
|

Predictors to Use Mobile Apps for Monitoring COVID-19 Symptoms and Contact Tracing: Survey Among Dutch Citizens

Abstract: Background eHealth apps have been recognized as a valuable tool to reduce COVID-19’s effective reproduction number. The factors that determine the acceptance of COVID-19 apps remain unknown. The exception here is privacy. Objective The aim of this article was to identify antecedents of acceptance of (1) a mobile app for COVID-19 symptom recognition and monitoring and (2) a mobile app for contact tracing, both by means of an online survey among Dutch cit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…The survey design was informed by prior literature on assessing participants’ intention to use digital interventions [ 29 , 30 ]. One researcher (with expertise in health informatics and implementation science) created the initial survey by adapting a subset of validated questions from a survey assessing participants’ intention to use mobile apps for COVID-19 symptom monitoring [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey design was informed by prior literature on assessing participants’ intention to use digital interventions [ 29 , 30 ]. One researcher (with expertise in health informatics and implementation science) created the initial survey by adapting a subset of validated questions from a survey assessing participants’ intention to use mobile apps for COVID-19 symptom monitoring [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The survey design was informed by prior literature on assessing participants’ intention to use digital interventions [ 29 , 30 ]. One researcher (with expertise in health informatics and implementation science) created the initial survey by adapting a subset of validated questions from a survey assessing participants’ intention to use mobile apps for COVID-19 symptom monitoring [ 30 ]. A cardiologist and 2 research team members (with training in public health and clinical research, respectively) reviewed the survey content and provided feedback on clarifying and simplifying the language of the introduction paragraph, the survey questions, and the response options.…”
Section: Methodsmentioning
confidence: 99%
“…In the Netherlands, upon getting a positive test result, more than 110,000 people agreed to share their results through Cor-onaMelder, which allowed the identification of 9000 additional positive virus cases (Hinch et al, 2020). Researchers from the University of Twente (Jansen-Kosterink et al, 2021) and the University of Tilburg (van der Laan et al, 2021) issued reports presenting their results of research on the adoption and use of the app. The researchers from Twente reported that the main reason people downloaded and used CoronaMelder was to control the spread of the virus, whereas the main reason for not downloading it was privacy.…”
Section: The Adoption and Usementioning
confidence: 99%
“…Themes: privacy concerns abound, but a majority indicate a willingness to download contact tracing apps. Many groups have assessed a population's willingness to download a contact tracing app, finding rates between 27 and 84% at different points in time, with different privacy and data sharing and usage situations and different populations, including Australia [21,22,30], China [56], a number of countries in Western Europe [1,3,35,38,46,56,69,97,100], and the US [1,3,4,38,39,56,60,72,90,101]. These works identified concerns thematically similar to ours, such as privacy concerns about sharing with the government, and correlations between willingness to download and COVID-19 concern levels or demographic information, e.g., age.…”
Section: Related Workmentioning
confidence: 99%